Study of the Inhibitory Effect of Probiotics on Staphylococcus Aureus Bacteria Isolated from the Milk of Cows Suffering from Mastitis (Indian Journal of Animal Production and Management, 2026)
This study was conducted to isolate and identify Staphylococcus aureus as one of the main causative agents of bovine mastitis, and to evaluate the inhibitory effect of lactic acid bacteria against the isolated strains. In addition, the antibiotic susceptibility of the isolates was determined using the disk diffusion method A total of 100 milk samples were collected from cows in different areas of Baghdad Governorate, including 40 samples from cows with acute mastitis 30 samples from cows with subclinical mastitis, and 30 samples from apparently healthy cows. Milk samples were cultured on blood agar followed by mannitol salt agar, and the isolates were identified based on microscopic, cultural, and biochemical characteristics The results showed that 10 isolates (10%) were identified as Staphylococcus aureus ,Sixty milk samples were negative by the California Mastitis Test, while no bacterial growth was observed in samples collected from healthy cows. Molecular detection revealed that 10 isolates (10%) were positive for the 16S rRNA gene, whereas 6 isolates (6%) were positive for the nuc gene Furthermore, all tested lactic acid bacteria isolates (Bifidobacterium bifidum, Lactobacillus acidophilus, and Lactobacillus rhamnosus) exhibited a clear inhibitory effect against Staphylococcus aureus at a concentration of 500 µL. However, no inhibitory activity was observed at lower concentrations (250 and 100 µL).
Keywords: conducted, isolate; Staphylococcus; aureus